Comment on "Excess pore pressure resulting from methane hydrate dissociation in marine sediments: A theoretical approach" by Wenyue Xu and Leonid N. Germanovich - art. no. B02103 - Sultan, Nabil (Journal of Geophysical Research, 2007)
While it is well accepted that gas hydrate dissociation at the base of the Gas Hydrate Stability Zone (GHSZ) can generate high excess pore pressure and leads to sediment deformation, the consequence in terms of pore pressure of the dissolution of the gas hydrate at the top of the Gas Hydrate Occurrence Zone (GHOZ) remains neglected. The purpose of this comment on Xu and Germanovich [2006] article is to demonstrate that gas hydrate dissolution in the GHSZ may generate excess pore pressure and to point out the risk related to hydrate dissolution at the top of the GHOZ.